Character Education Management Model Development in Society - Teti Muliawati; Asep Sumarna; Aan Hasanah; Bambang Samsul Arifin (STAI Miftahul Ula Nganjuk, 2023)
The purpose of this study is to identify the moral principles that the social institution Istiqamah Bandung Istitution has implanted. This study is a qualitative investigation. The data for this type of case study research was gathered through interviews with the board of foundations about the implementation of character education and the management model of character education, as well as observation to track the character education development model. Results study, which focuses on character development and management, is continuously done in the social, religious, and educational sectors of employment. The Bandung Istiqamah Istitution emphasizes a number of qualities in the formation and development of character. These principles include: religion, honesty, decency, discipline, toleration, concern for others, and respect for accomplishment. The inhabitants of the Istiqamah Bandung Foundation, Islamic law based on the Qur'an and Sunnah, and the Foundation's areas of operation are the foundational elements of the Foundation's character education program.